A Suicidal Death which was Treated and Masqueraded as an Accidental Death - Chouksey , V; Baveja , V S; Sabu , N; Nigam , M (Journal of Indian Academy of Forensic Medicine, 2023)
The work of an autopsy surgeon revolves not only around performing autopsy of the body but it also requires ruling out every single  possibility, relevant or remote, even if the possibility of it, actually happening is as thin as a whisker before coming to formulation of  opinion. It is not uncommon for an autopsy surgeon to come across cases wherein there is a stark contrast between what is being claimed  and that which is evident. History is manipulated for a plethora of reasons, one prominent reason being eschewing the societal stigma  associated with suicide as a consequence of probable sexual assault in a rural place. This is one such case wherein a 15 years old female was  brought to the hospital with a history of being bitten by a snake which was witnessed by the deceased's father. Thereafter, treatment was  provided at the hospital after taking the history into account. After almost 48 hours of survival, she was certified dead and owing to the  unnatural death, an autopsy was deemed necessary. The lack of evidence supporting snake bite, certain incidental findings during the  autopsy along with the reconstruction of events based on the circumstantial evidence led to the conclusion that this was a case of suicidal  death caused by ingestion of a poisonous substance and not that of an accidental death as a consequence of snake bite.
Keywords: Misleading history; Organophosphate poisoning; Snake bite; Suicidal death autopsy